1996
DOI: 10.1507/endocrj.43.403
|View full text |Cite
|
Sign up to set email alerts
|

Inhibin .ALPHA., .BETA.A and .BETA.B Subunit Messenger Ribonucleic Acid Levels in Cultured Rat Pituitary: Studies by a Quantitative RT-PCR.

Abstract: Abstract. Recent studies have demonstrated that inhibins and activins both play not only endocrine roles but also local regulatory roles in gonadotoropin secretion. There has been controversy as to the subtype of rat pituitary inhibin/activin.We studied the levels of inhibin a, 1'A and f subunit mRNAs by a quantitative reverse transcription-polymerase chain reaction (RT-PCR) and the changes in their levels by adding inhibin a, fA and fiB mRNA antisense oligonucleotides and inhibin A, activin A or GnRH to cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 20 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…The mRNA encoding the activin ␤A subunit gene has been detected in rat pituitary gland (97,415,459). Its levels change after oophorectomy (498), as well as following treatment with luteinizing hormone (LH) or progesterone (415), indicating a possible regulation by ovarian steroids, peptide hormones, or both.…”
Section: Pituitary Glandmentioning
confidence: 99%
“…The mRNA encoding the activin ␤A subunit gene has been detected in rat pituitary gland (97,415,459). Its levels change after oophorectomy (498), as well as following treatment with luteinizing hormone (LH) or progesterone (415), indicating a possible regulation by ovarian steroids, peptide hormones, or both.…”
Section: Pituitary Glandmentioning
confidence: 99%
“…Together with the high levels of ActR2, ALK2, and ALK4 mRNA observed during the secondary surge of FSH (Fafioffe et al 2004), these results In cultured ewe pituitary cells, treatment of cells with GnRH for 6 h did not modify the level of activin bB mRNA. Similarly, in rat pituitary cells, chronic GnRH or rapid pulse frequency of GnRH did not affect activin bB mRNA levels in contrast to low pulse frequency (Demura et al 1996, Dalkin et al 1999. Treatment of pituitary cells with E 2 for 48 h increased the level of activin bB mRNA.…”
Section: Discussionmentioning
confidence: 76%
“…Many previous studies have demonstrated the presence of inhibin α-subunit mRNA and protein expressions in the anterior pituitary cells [1], [6][7]. The proposed function of inhibin α-subunit is to primarily modulate FSH production through its endocrine feedback module [7].…”
Section: Introductionmentioning
confidence: 99%